Pang's death loss to PLKN - Dept head - Borneo Post, (KK) (Borneo Post (KK), 2013)
KULIM: The death of novelist-cum-activist Pang Soon Gi who drowned on March 30 in Langkawi, is a loss to the National Service Training Department (JLKN).